Glass with low dielectric property and application thereof

By adjusting the glass composition and processing technology, glass with low dielectric constant and suitable thermal expansion coefficient was prepared, which solved the problem of warping of existing glass materials in chip packaging and achieved efficient TGV through-hole processing.

CN119822636APending Publication Date: 2025-04-15ZHEJIANG XINGKE OPTOELECTRONICS TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411958538.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing glass materials contain a large amount of alkali metal in chip packaging, which leads to excessive thermal expansion coefficient, and the difference with the silicon substrate leads to warping.

Method used

By controlling the glass composition ratio and alkaline earth metal oxide ratio, glass with low dielectric constant and dielectric loss was prepared, and TGV through holes were processed through laser induction and acid etching technology to ensure that the thermal expansion coefficient of the glass is close to that of the silicon substrate.

Benefits of technology

The low dielectric properties of the glass and the appropriate thermal expansion coefficient are achieved, the warping problem is avoided, and TGV through holes with high depth diameter ratio are obtained through efficient etching technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822636A_ABST
    Figure CN119822636A_ABST
Patent Text Reader

Abstract

The invention relates to low-dielectric-property glass and application thereof, and belongs to the technical field of semiconductor packaging. Comprising the following components in percentage by weight: 61%-70% of SiO2, 12%-14.5% of Al2O3, 11.5%-15.5% of B2O3, 1%-2% of MgO, 3%-6% of CaO, 1%-3% of SrO, 0.5%-1% of BaO and 0.5%-2% of Y2O3. L = MAX ([MgO], [CaO], [SrO], [BaO])-MIN ([MgO], [CaO], [SrO], [BaO]), and L is greater than or equal to 2 and less than or equal to 5.5; s = ([MgO] + [CaO] + [SrO] + [BaO]), 6 < = S < = 12; 0.3 < = L / S < = 0.6; the glass obtained by controlling the component proportion and the alkaline earth metal oxide proportion has low dielectric constant and dielectric loss; and has a coefficient of thermal expansion close to that of the silicon substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of semiconductor packaging technology, and in particular to a low dielectric performance glass and its application. Background Art

[0002] The business pressure of data centers is increasing, and the demand for reducing power consumption and the integration of optical module packaging is increasing. Although silicon-based high-density capacitors can meet the high capacitance density and high integration of such scenarios, the loss caused by the substrate and the cost of deep silicon etching process have also become considerations in the industry. Glass substrate TGV technology has become a hot research topic as an alternative: its excellent insulation, adjustable coefficient of thermal expansion (CTE), availability of panel-level size and excellent high-frequency electrical performance make it an ideal substrate for integrated passive devices.

[0003] Someone proposed a glass and its through-hole processing method and application. The glass contains: SiO2: 63% to 75%; Al2O3: 3% to 12%; Na2O: 2% to 10%; K2O: 3% to 10%, and the balance is additives. The glass has the low dielectric constant and dielectric loss required for chip packaging, and the etching rate ratio between the induced area and the non-induced area is high. The etching rate is high when the laser induced etching technology is used to process the TGV through hole. However, it contains a large amount of alkali metals, which makes the glass network loose, resulting in a larger thermal expansion coefficient, and a greater difference with silicon in semiconductor packaging, which is prone to warping and other problems. Summary of the invention

[0004] The present application provides a low dielectric glass and application thereof, so that the low dielectric glass has a lower expansion coefficient.

[0005] In a first aspect, the present application provides a low dielectric glass, wherein the components of the glass include, by mass percentage: SiO2: 61% to 70%, Al2O3: 12% to 14.5%, B2O3: 11.5% to 15.5%, MgO: 1% to 2%, CaO: 3% to 6%, SrO: 1% to 3%, BaO: 0.5% to 1% and Y2O3: 0.5 to 2%, and unavoidable impurities;

[0006] And the glass satisfies:

[0007] L=MAX([MgO],[CaO],[SrO],[BaO])-MIN([MgO],[CaO],[SrO],[BaO]), 2≤L≤5.5;

[0008] S=([MgO]+[CaO]+[SrO]+[BaO]), 6≤S≤12;

[0009] 0.3≤L / S≤0.6; wherein [MgO] is the mass percentage of MgO in the glass, [CaO] is the mass percentage of CaO in the glass, [SrO] is the mass percentage of SrO in the glass, and [BaO] is the mass percentage of BaO in the glass.

[0010] As an optional embodiment, in the glass:

[0011] The mass percentage of SiO2 is 64% to 67%; and / or

[0012] The mass percentage of Al2O3 is 12.5% ​​to 14%; and / or

[0013] The mass percentage of B2O3 is 12.5% ​​to 14.5%; and / or

[0014] The mass percentage of MgO is 1.2% to 1.8%; and / or

[0015] The mass percentage of CaO is 4% to 5%; and / or

[0016] The mass percentage of SrO is 11% to 14%; and / or

[0017] The mass percentage of BaO is 0.6% to 0.9%; and / or

[0018] The mass percentage of Y2O3 is 1% to 1.5%.

[0019] As an optional implementation, 3≤L≤5.5; and / or

[0020] 8≤S≤10; and / or

[0021] 0.4≤L / S≤0.6.

[0022] As an optional implementation, the glass further comprises a clarifier, and the mass percentage of the clarifier in the glass is no more than 2%.

[0023] As an optional implementation, at 1 MHz, the dielectric constant of the glass is less than 4.8, and the dielectric loss of the glass is less than 0.001.

[0024] In a second aspect, the present application provides a component, which includes the glass provided in the first aspect, and the glass is provided with a through hole.

[0025] In a third aspect, the present application provides a method for preparing the component provided in the second aspect, the method comprising:

[0026] Obtaining glass, wherein the glass is the glass provided in the first aspect;

[0027] The glass is subjected to laser induction treatment and etching treatment to obtain a component.

[0028] As an optional implementation, the pulse energy of the laser induced treatment is 500nJ to 1000nJ.

[0029] As an optional implementation manner, the etching solution for the etching treatment comprises hydrofluoric acid, and the mass fraction of the hydrofluoric acid is 3% to 30%; and / or

[0030] The temperature of the etching process is 25-35° C.; and / or

[0031] The etching treatment takes 10 to 60 minutes.

[0032] In a fourth aspect, the present application provides an application of the glass provided in the first aspect in a glass transfer plate and / or a glass chip.

[0033] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0034] The glass provided in the embodiment of the present application has a low dielectric constant and dielectric loss obtained by controlling the composition ratio and the proportion of alkaline earth metal oxides; and has a thermal expansion coefficient close to that of a silicon substrate. After laser induction and acid etching, a TGV through hole with a high aspect ratio can be obtained through the glass. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0036] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0037] Figure 1 A flowchart of the method provided in the embodiment of the present application. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0039] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0040] In recent years, with the rapid development of informatization and digitalization, artificial intelligence and big data cloud computing require more powerful computing power, and the corresponding semiconductor circuit integration is getting higher and higher, which in turn puts forward new requirements for packaging technology. Advanced packaging technology has higher I / O density, faster signal transmission speed and better electrical and thermal performance. While improving chip performance, it also reduces chip power consumption and volume, and improves reliability and production efficiency.

[0041] The key to chip packaging lies in the number of chips fixed on the chip substrate. The more chips there are, the more transistors the chip has, the stronger its functions are, and the better its performance is. Therefore, how to accommodate more transistors in a limited size has become the development direction that the entire industry is constantly exploring. The most mainstream chip substrate at present is the organic material substrate, which has been used in the chip packaging field for many years due to its low processing difficulty and low production cost. However, with the upgrading of global computing power demand, the continuous development of advanced packaging technologies such as 2.5D / 3D and Chiplet, and the continuous improvement of chip requirements for signal transmission speed, power transmission efficiency, and substrate stability, the plastic substrate (organic material substrate) currently used by the industry will reach its capacity limit, and its relatively rough surface will affect the inherent performance of ultra-fine circuits. In advanced packaging, it faces problems such as solder joint reliability and packaging heat dissipation. In addition, organic materials may shrink or warp during the chip manufacturing process, resulting in chip defects. As more silicon chips are packaged on plastic substrates, the risk of warping will also increase. Therefore, traditional organic material substrates can no longer meet the packaging needs of high-performance chips.

[0042] Semiconductor silicon substrates are widely used in various electronic devices, such as microprocessors, memory, integrated circuits, solar panels, etc., and are considered to be one of the most advanced technologies in the current semiconductor industry. However, the production of TSV in traditional silicon substrates uses silicon etching technology, which requires oxidation of insulating layers, thin wafer holding and other technologies, and has high manufacturing costs; at the same time, silicon materials are semiconductor materials, and when the transmission line transmits signals, the signal and the substrate material have a strong electromagnetic coupling effect, which will produce eddy currents, resulting in poor signal integrity (insertion loss, crosstalk, etc.) and poor electrical performance. At the same time, the number of silicon-based packaged transistors is about to reach the technical limit.

[0043] In recent years, through glass via (TGV) technology as an alternative to TSV is becoming a research hotspot in the semiconductor industry. Compared with traditional organic substrates, glass substrates have significant advantages in mechanical, physical, and optical aspects, and have begun to attract attention in the field of advanced packaging. In addition, glass materials have the following unique properties: excellent electrical performance, glass substrates can effectively reduce power loss and energy consumption during signal transmission, thereby greatly enhancing the transmission efficiency and computing power of chips and improving chip performance; high flatness, the unique flatness of glass substrates can significantly improve the focus depth of lithography and greatly increase the interconnection density between chips. The number of openings on the same area of ​​glass substrates far exceeds that of organic material substrates. The interval between TGVs can be less than 100μm, and the interconnection density is increased by more than 10 times; high temperature resistance, glass substrates also have stronger thermal and mechanical stability, and the thermal expansion coefficient is similar to that of chips. It is not easy to produce deformation problems such as warping and fracture at high temperatures, which increases chip reliability. It can achieve a larger package size. Glass substrates can make the chip package size larger to accommodate more transistors. According to statistics, 50% more transistors can be placed on glass substrates, greatly improving the packaging density. Compared with organic materials and silicon materials, glass has a higher Young's modulus and hardness, and its thermal expansion coefficient is adjustable, which can reduce the stress inside the chip. Therefore, glass substrates are more suitable for high-speed signal interconnection applications, which can reduce interconnection loss and distortion and increase signal transmission rate.

[0044] The core of glass substrate in the application of advanced packaging technology is TGV technology. TGV corresponds to TSV. As a material that may replace silicon substrate, it is considered to be the key technology of next-generation three-dimensional integration and an upgrade of TSV technology. With its excellent high-frequency electrical properties, low cost of large-size ultra-thin glass substrates, simple process flow, strong mechanical stability and other advantages, TGV technology has broad development and application prospects, especially in the fields of RF chips, high-end MEMS sensors, high-density system integration, etc. It has unique advantages and is considered to be one of the first choices for the next-generation 5G and 6G high-frequency chip 3D packaging. With the advancement of technology and the promotion of the market, TGV is expected to play a more important role in the future semiconductor packaging field. A large number of scientific researchers have carried out a lot of related process technology research work on TGV, and have made certain progress in high-density TGV hole formation, TGV metal filling, glass substrate integrated waveguide, chip-to-chip optical interconnection, filters, RF modules, etc.

[0045] Someone proposed a glass and its through-hole processing method and application. The glass contains: SiO2: 63% to 75%; Al2O3: 3% to 12%; Na2O: 2% to 10%; K2O: 3% to 10%, and the balance is additives. The glass has the low dielectric constant and dielectric loss required for chip packaging, and the etching rate ratio between the induced area and the non-induced area is high. The etching rate is high when the laser induced etching technology is used to process the TGV through hole. However, it contains a large amount of alkali metals, which makes the glass network loose, resulting in a larger thermal expansion coefficient, and a greater difference with silicon in semiconductor packaging, which is prone to warping and other problems.

[0046] The present application intends to provide a low dielectric glass and its application, by controlling the composition ratio and the ratio of alkaline earth metal oxides, so that the low dielectric glass has a lower thermal expansion coefficient, so that it is close to the thermal expansion coefficient of the silicon substrate. After laser induction and acid etching, a TGV through hole with a high aspect ratio can be obtained.

[0047] The embodiment of the present application provides a low dielectric glass, wherein the components of the glass include, by mass percentage: SiO2: 61% to 70%, Al2O3: 12% to 14.5%, B2O3: 11.5% to 15.5%, MgO: 1% to 2%, CaO: 3% to 6%, SrO: 1% to 3%, BaO: 0.5% to 1% and Y2O3: 0.5 to 2%, and unavoidable impurities;

[0048] And the glass satisfies:

[0049] L=MAX([MgO],[CaO],[SrO],[BaO])-MIN([MgO],[CaO],[SrO],[BaO]), 2≤L≤5.5;

[0050] S=([MgO]+[CaO]+[SrO]+[BaO]), 6≤S≤12;

[0051] 0.3≤L / S≤0.6; wherein [MgO] is the mass percentage of MgO in the glass, [CaO] is the mass percentage of CaO in the glass, [SrO] is the mass percentage of SrO in the glass, and [BaO] is the mass percentage of BaO in the glass.

[0052] In some embodiments, in the glass: the mass percentage of SiO2 is 64% to 67%; the mass percentage of Al2O3 is 12.5% ​​to 14%; the mass percentage of B2O3 is 12.5% ​​to 14.5%; the mass percentage of MgO is 1.2% to 1.8%; the mass percentage of CaO is 4% to 5%; the mass percentage of SrO is 11% to 14%; the mass percentage of BaO is 0.6% to 0.9%; the mass percentage of Y2O3 is 1% to 1.5%.

[0053] In some embodiments, 3≤L≤5.5; 8≤S≤10; 0.4≤L / S≤0.6.

[0054] In the present application, SiO2 is a network forming body of the base glass, which can form glass alone and is one of the necessary components. It gives the base glass better chemical stability, mechanical properties and forming properties. At the same time, it can reduce the dielectric properties of the base glass. The SiO2 content is at least 61%; but too high SiO2 also slows down the etching rate of the uninduced area of ​​the glass after laser induction, resulting in a conical pore morphology, so the SiO2 content is up to 70%. Preferably, the mass percentage of SiO2 is 64% to 67%.

[0055] In the present application, the volume of aluminum oxide tetrahedron formed by Al2O3 in the glass is larger than that of silicon oxide tetrahedron in the glass, and the volume of the glass expands, thereby reducing the density of the glass, and at the same time, it can effectively reduce the dielectric properties. The Al2O3 content in the base glass is at least 12%; however, Al2O3 is an extremely refractory oxide, which can quickly increase the high-temperature viscosity of the glass, making it more difficult to clarify and homogenize the glass, and greatly increasing the concentration of bubble defects in the glass; therefore, the maximum Al2O3 content in the base glass is 14.5%. Preferably, the mass percentage of Al2O3 is 12.5% ​​to 14%.

[0056] In the present application, B2O3 is also a glass-forming oxide, and the boron-oxygen tetrahedron [BO4] is a frame structure with a tight structure, which can effectively reduce the dielectric constant. However, if the B2O3 content continues to increase, there is not enough free oxygen in the glass, the boron-oxygen triangle [BO3] in the layered structure increases, the boron-oxygen tetrahedron [BO4] content decreases, the glass network structure is loose, the chemical properties are unstable, and the excessive boron oxide content increases in volatility, which can easily cause uneven glass composition. Therefore, in the present application, B2O3 is controlled between 11.5% and 15.5%, and preferably, the mass percentage of B2O3 is 12.5% ​​to 14.5%.

[0057] In the present application, MgO, CaO, SrO, and BaO are all alkaline earth metal oxides. Their addition is beneficial to effectively reduce the high-temperature viscosity of glass, thereby improving the solubility and formability of glass. However, excessive content will cause the glass network to break and the dielectric properties to deteriorate. In the present application, MgO: 1-2%; CaO: 3-6%; SrO: 1-3%; BaO: 0.5-1%; and the total amount S=([MgO]+[CaO]+[SrO]+[BaO]) satisfies 6≤S≤12; at the same time, each alkaline earth metal needs to satisfy L=MAX([MgO],[CaO],[SrO],[BaO])-MIN([MgO],[CaO],[SrO],[BaO]), 2≤L≤5.5, 0.3≤L / S≤0.6. Wherein, [MgO] is the mass percentage of MgO in the glass, [CaO] is the mass percentage of CaO in the glass, [SrO] is the mass percentage of SrO in the glass, and [BaO] is the mass percentage of BaO in the glass. This formula is used to characterize the difference in content between various alkaline earth metals. The greater the difference, the better the dielectric properties.

[0058] In the present application, Y2O3 plays a role in reducing dielectric loss, and its accumulation effect on the glass network is dominant, and the glass structure undergoes a certain degree of contraction, so that the movement of foreign ions in the glass is restricted. In addition, it can fill in the gaps to make it difficult for other foreign cations to migrate, thereby reducing the conductivity loss in the glass; at the same time, the degree of polymerization and rigidity of the glass structure also increase under the action of rare earth ions. Under the action of an external electric field, the degree of polarization deformation of the glass network is reduced, and the relaxation loss is also reduced, and the dielectric loss of the glass is reduced. However, when the doping amount is greater than 2%, the excessive introduction of free oxygen causes the glass network to depolymerize, the structure becomes loose, the migration ability of foreign ions in the glass is improved, the structural loss and the conductivity loss are increased, resulting in an increase in dielectric loss. Preferably, the mass percentage of Y2O3 is 1% to 1.5%.

[0059] The glass obtained by controlling the composition ratio and the proportion of alkaline earth metal oxides has a low dielectric constant and dielectric loss; and has a thermal expansion coefficient close to that of a silicon substrate. After laser induction and acid etching, a TGV through hole with a high aspect ratio can be obtained through the glass.

[0060] In some embodiments, depending on the glass preparation process, the composition may further contain a clarifier for melting the glass, and the clarifier is preferably at least one of sulfate, nitrate, halide, tin oxide, stannous oxide, and cerium oxide; based on the weight of each component, the content of the clarifier is not more than 2wt%, preferably 0.05wt%-0.8wt%. There is no particular limitation on the specific selection of the clarifier, and it can be any commonly used selection in the art, for example, the sulfate can be sodium sulfate, the nitrate can be sodium nitrate and / or potassium nitrate, the chloride can be sodium chloride and / or strontium chloride, and the fluoride can be calcium fluoride.

[0061] In some embodiments, at 1 MHz, the dielectric constant of the glass is less than 4.8, the dielectric loss of the glass is less than 0.001, and the dielectric properties of the glass remain unchanged after being etched with HF acid.

[0062] Based on the same inventive concept, an embodiment of the present application further provides a component, which includes the glass provided above, and a through hole is provided on the glass.

[0063] This component is implemented based on the above-mentioned glass. The specific content of the glass can refer to the above-mentioned embodiment. Since this component adopts part or all of the technical solutions of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be repeated here one by one.

[0064] Figure 1 A flow chart of the method provided in the embodiment of the present application is as follows: Figure 1 As shown, the embodiment of the present application also provides a method for preparing a component, the method comprising:

[0065] S1. Obtaining glass, wherein the glass is the glass provided in the first aspect;

[0066] S2. Performing laser induction treatment and etching treatment on the glass to obtain a component.

[0067] Specifically, in this embodiment, the glass is subjected to laser induction treatment, and the glass after laser induction treatment is immersed in an etching solution for etching to form a through hole. The laser induction treatment uses a pulsed laser with a pulse energy of 500nJ to 1000nJ to induce the denaturation of the glass. The etching treatment uses HF acid to etch the glass after laser induction, the mass fraction of HF acid is 3% to 30%, the temperature is 25 to 35°C, and the time is 10min to 60min.

[0068] In some embodiments, the glass can be chemically strengthened as needed, which can be achieved by sodium-potassium ion exchange. The chemically strengthened glass can have better performance.

[0069] After chemical strengthening, a chemically strengthened glass is formed, the surface of the chemically strengthened glass has a compressive stress layer, and the inside has a tensile stress layer, and the composition at the center of the chemically strengthened glass includes, by mass percentage, SiO2: 61% to 70%, Al2O3: 12% to 14.5%, B2O3: 11.5% to 15.5%, MgO: 1% to 2%, CaO: 3% to 6%, SrO: 1% to 3%, BaO: 0.5% to 1% and Y2O3: 0.5 to 2%, and inevitable impurities;

[0070] And the glass satisfies:

[0071] L=MAX([MgO],[CaO],[SrO],[BaO])-MIN([MgO],[CaO],[SrO],[BaO]), 2≤L≤5.5;

[0072] S=([MgO]+[CaO]+[SrO]+[BaO]), 6≤S≤12;

[0073] 0.3≤L / S≤0.6; wherein [MgO] is the mass percentage of MgO in the glass, [CaO] is the mass percentage of CaO in the glass, [SrO] is the mass percentage of SrO in the glass, and [BaO] is the mass percentage of BaO in the glass.

[0074] The above-mentioned glass and / or chemically strengthened glass can be applied to the fields of glass transfer plates, glass chips, etc.

[0075] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0076] Examples and Comparative Examples

[0077] A through-hole glass, the preparation method of which comprises the following steps:

[0078] 1) Preparation of basic glass samples: Weigh and evenly mix the raw materials such as quartz sand, aluminum oxide, boron oxide, magnesium oxide, calcium carbonate, barium carbonate, strontium carbonate, and yttrium oxide to obtain a uniform batch; then transfer the batch to a platinum crucible of about 1500 ml, place the platinum crucible in a silicon-molybdenum rod high-temperature furnace, gradually heat it to 1500℃~1650℃, keep the temperature for 2~6 hours, and accelerate the discharge of glass bubbles by stirring. After melting, pour the molten liquid into a heat-resistant stainless steel mold for molding, then take out the glass block and move it into a box-type annealing furnace for heat treatment at 600℃ for 4 hours, and then naturally cool it to room temperature to obtain basic glass. The glass block is cut, ground and polished to prepare a 20*5*1mm sample.

[0079] The composition (in mass percentage) of the glass provided in each embodiment and comparative example is shown in Table 1.

[0080] Table 1

[0081]

[0082] 2) Laser induced etching of through holes: The above glass samples were irradiated with a laser beam of E = 55 uJ / pulse, pulse width τ = 16 ps, and repetition frequency f = 500 kHz. The modified glass samples were then placed in a 5% HF acid solution and ultrasonically bathed at 30°C for 30 min, followed by a 5 min deionized water rinse.

[0083] Test the performance of glass.

[0084] Dielectric constant and dielectric loss test: According to the test method in ASTM-D150, the glass was sliced, ground and polished, and then its dielectric constant and dielectric loss were tested. The results are shown in Table 2

[0085] Dielectric property acid resistance test: The basic glass sample and the sample immersed in 5% by mass HF for a certain period of time were subjected to dielectric property tests. The results are shown in Table 3.

[0086] Table 2

[0087]

[0088]

[0089] Table 3

[0090]

[0091] As can be seen from the above table, by controlling the composition ratio and the proportion of alkaline earth metal oxides, the glass obtained can obtain a TGV through hole with a high aspect ratio after laser induction and acid etching. In addition, the glass has a low dielectric constant and dielectric loss; and a thermal expansion coefficient close to that of the silicon substrate. At a frequency of 1MHz, the dielectric constant is less than 5, the dielectric loss is less than 0.001, and after acid etching, the dielectric constant and dielectric loss basically remain unchanged. This glass is suitable for glass transfer boards and electronic product chips.

[0092] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0093] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b or c" or "at least one of a, b and c" can both mean: a, b, c, a-b (i.e. a and b), a-c, b-c, or a-b-c, where a, b and c can be single or multiple.

[0094] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A low dielectric glass, characterized in that: The glass comprises, by mass percentage, SiO2: 61% to 70%, Al2O3: 12% to 14.5%, B2O3: 11.5% to 15.5%, MgO: 1% to 2%, CaO: 3% to 6%, SrO: 1% to 3%, BaO: 0.5% to 1% and Y2O3: 0.5 to 2%, and unavoidable impurities; And the glass satisfies: L=MAX([MgO],[CaO],[SrO],[BaO])-MIN([MgO],[CaO],[SrO],[BaO]), 2≤L≤5.5; S=([MgO]+[CaO]+[SrO]+[BaO]), 6≤S≤12; 0.3≤L / S≤0.6; wherein [MgO] is the mass percentage of MgO in the glass, [CaO] is the mass percentage of CaO in the glass, [SrO] is the mass percentage of SrO in the glass, and [BaO] is the mass percentage of BaO in the glass.

2. The low dielectric glass according to claim 1, characterized in that: In the glass: The mass percentage of SiO2 is 64% to 67%; and / or The mass percentage of Al2O3 is 12.5% ​​to 14%; and / or The mass percentage of B2O3 is 12.5% ​​to 14.5%; and / or The mass percentage of MgO is 1.2% to 1.8%; and / or The mass percentage of CaO is 4% to 5%; and / or The mass percentage of SrO is 11% to 14%; and / or The mass percentage of BaO is 0.6% to 0.9%; and / or The mass percentage of Y2O3 is 1% to 1.5%.

3. The low dielectric glass according to claim 1 or 2, characterized in that: 3≤L≤5.5; and / or 8≤S≤10; and / or 0.4≤L / S≤0.

6.

4. The low dielectric glass according to claim 1 or 2, characterized in that: The glass also includes a clarifier, and the mass percentage of the clarifier in the glass is no more than 2%.

5. The low dielectric glass according to claim 1 or 2, characterized in that: At 1 MHz, the dielectric constant of the glass is less than 4.8, and the dielectric loss of the glass is less than 0.

001.

6. A component, characterized in that: The component comprises the glass according to any one of claims 1 to 5, wherein the glass is provided with a through hole.

7. A method for preparing the component according to claim 6, characterized in that: The method comprises: Obtaining glass, wherein the glass is the glass according to any one of claims 1 to 7; The glass is subjected to laser induction treatment and etching treatment to obtain a component.

8. The method for preparing a component according to claim 7, characterized in that: The pulse energy of the laser induced treatment is 500nJ to 1000nJ.

9. The method for preparing a component according to claim 7 or 8, characterized in that: The etching solution for the etching process comprises hydrofluoric acid, and the mass fraction of the hydrofluoric acid is 3% to 30%; and / or The temperature of the etching process is 25-35° C.; and / or The etching treatment takes 10 to 60 minutes.

10. Use of the glass according to claims 1 to 5 in a glass transition plate and / or a glass chip.